Manufacturing method of welded joint and flux-cored cut wire for filling groove

The use of a flux-containing cut wire with specific elements addresses high-temperature cracking in high-strength steel welding, enhancing resistance and efficiency by forming stable sulfides that prevent cracks, thus improving weld quality and reducing preheating requirements.

JP7623565B2Active Publication Date: 2025-01-29NIPPON STEEL CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020169993
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-07
Publication Date
2025-01-29
Estimated Expiration
2040-10-07

AI Technical Summary

Technical Problem

Existing welding technologies for high-strength steel structures face challenges in preventing high-temperature cracks during large heat welding, particularly in narrow spaces, due to the formation of low-melting point compounds and sulfur elements, which are not adequately addressed by current methods that control impurities like P and S.

Method used

A flux-containing cut wire is used in the welding process, filled with specific elements like CA, MG, TI, ZR, and REM as oxides or alloys, along with controlled impurity levels of P and S, to form sulfides that enhance high-temperature resistance and prevent cracking.

Benefits of technology

The method effectively prevents high-temperature cracks in high-strength steel welding, improving welding efficiency and reducing preheating burdens while maintaining weld metal strength and toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623565000005
    Figure 0007623565000005
  • Figure 0007623565000006
    Figure 0007623565000006
  • Figure 0007623565000007
    Figure 0007623565000007
Patent Text Reader

Abstract

To provide a method for manufacturing a weld joint which can prevent high-temperature cracking while reducing a burden of a preheating work, and can advantageously obtain a weld joint with high weld efficiency, and a flux-cored cut wire used in the same.SOLUTION: A method for filling an initial layer in a groove with a flux-cored cut wire having a steel sheath and a flux that is made to fill the inside of the steel sheath, and welding the groove, in which the flux contains a strong deoxidizing element (Ca, Mg, Ti, Zr and REM) as an oxide and / or an alloy; and a flux-cored cut wire used in the same.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a welded joint in which a cut wire is filled into a groove provided between base materials and welded, and to a flux-cored cut wire for filling the groove used in the method. [Background technology]

[0002] In recent years, in the field of manufacturing large steel structures such as ships, steel frames, and bridges, the strength of steel plates has been increased in order to achieve both weight reduction and high performance. Also, from the viewpoint of improving construction efficiency, there is a demand for welding materials that can handle high heat input welding such as one-sided welding and double-sided single layer welding for submerged arc welding (SAW), which is mainly used for plate joint welding.

[0003] In general, high-tensile steel welding materials for submerged arc welding have excellent tensile properties due to the addition of alloying elements, but the added elements cause a problem of reduced hot cracking resistance of the weld metal. When the welding heat input is increased, the bead shape tends to become no-bead, especially in narrow gap welding, and the risk of hot cracking increases.

[0004] Hot cracks that occur in weld metal occur when low-melting-point compounds such as P and S contained in the weld metal segregate between dendrites or at austenite grain boundaries during solidification, and welding shrinkage strain is added to the segregation. Therefore, one effective measure to prevent hot cracks is to keep impurities such as low-melting-point compounds such as P and S to 100 ppm or less. However, this method requires high costs for impurity removal, which increases manufacturing costs, so there is a demand for technology that can prevent hot cracks even at general impurity levels.

[0005] In addition, when performing large heat input construction (large heat input welding) in submerged arc welding, in order to achieve high deposition efficiency (increase in deposition amount) and control of penetration depth, it is often necessary to use a groove filler, also known as cut wire, which is formed by cutting a thin-diameter steel wire into small pieces of a specified length and has a circular cross section.

[0006] For example, Patent Document 1 discloses a groove filler that ensures hot crack resistance and good toughness by reducing the Ni content of the cut wire and adding Mo (see paragraph 0015). Patent Document 2 discloses a technology that prevents first-layer hot cracking by using a filler with a reduced C content to suppress dilution of the base material (see paragraph 0012).

[0007] However, as the strength of steel plates and weld metals continues to increase, and there is a demand for the use of high alloys with high alloying element contents and for high heat input welding, S is mixed in from the raw materials for welding materials and steel plates depending on their cleanliness. Furthermore, as the amount of S mixed in increases, the temperature difference (ΔT) between the solidus and liquidus becomes larger. In high alloys, which already have a large temperature difference (ΔT), the temperature difference (ΔT) becomes too large and hot cracking becomes more likely to occur. Therefore, the technologies described in Patent Documents 1 and 2 above do not necessarily provide sufficient resistance to hot cracking, and there is a demand for the development of new technologies to prevent hot cracking. In addition, the techniques of Patent Document 1 and Patent Document 2 described above are not techniques for fixing elemental sulfur (S) which forms a low melting point compound, and therefore cannot suppress hot cracking in the weld metal when butt solidification occurs, which is a solidification form in which hot cracking is likely to occur due to high welding heat input. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2008-264,812 A [Patent Document 2] JP 2016-022,502 A Summary of the Invention [Problem to be solved by the invention]

[0009] As the strength of steel plates and weld metals continues to increase, the inventors have conducted extensive research into a method for manufacturing a welded joint that can prevent hot cracking while reducing the burden of preheating, even in the case of large heat input welding or high alloys. As a result, they have found that by previously loading flux containing a predetermined strong deoxidizing element into a cut wire that is used to fill the groove between base materials during welding, and by using this flux-cored cut wire for welding, the strong deoxidizing element can be retained in the weld metal as sulfides with a good yield, thereby solving the above-mentioned problems, and have completed the present invention.

[0010] Therefore, an object of the present invention is to provide a method for manufacturing a welded joint that can prevent hot cracking while reducing the burden of preheating, and can obtain a welded joint with high welding efficiency. Another object of the present invention is to provide a flux-cored cut wire for use in the method for producing such a welded joint. [Means for solving the problem]

[0011] That is, the gist of the present invention is as follows. (1) A method for manufacturing a welded joint in which a cut wire is filled into a groove provided between base materials and welded, A method for welding by filling a first layer in the groove with a flux-cored cut wire having a steel sheath and flux filled inside the steel sheath, A method for producing a welded joint, characterized in that the flux contains one or more strong deoxidizing elements selected from the group consisting of Ca, Mg, Ti, Zr, and REM as an oxide and / or alloy. (2) The flux-cored cut wire has a mass ratio to the total mass of the flux-cored cut wire of: The total content of the strong deoxidizing elements is 0.1% or more and 98.0% or less, and the contents of the chemical components consisting of C, Si, Mn, Cu, Ni, Cr, Mo, Nb, V, Al, B, and Bi are C: 0.120% or less, Si: 2.00% or less, Mn: 3.50% or less, Cu: 5.00% or less, Ni: 5.00% or less, Cr: 5.00% or less, Mo: 5.00% or less, Nb: 0.50% or less, V: 0.500% or less, Al: 1.70% or less, B: 0.020% or less, and Bi: 0.030% or less, The method for producing a welded joint according to (1) above, characterized in that the contents of impurity elements consisting of P and S are P: 0.030% or less and S: 0.020% or less. (3) A method for manufacturing a welded joint as described in (1) or (2) above, characterized in that after the flux-cored cut wire is filled into the initial layer in the groove, a solid cut wire obtained by cutting a solid wire is filled and welded. (4) The method for producing a welded joint according to any one of (1) to (3) above, characterized in that the welding is submerged arc welding or gas shielded arc welding.

[0012] (5) A cut wire for groove filling, which is used to fill a groove between base materials to manufacture a welded joint, A steel sheath and a flux filled inside the steel sheath, A flux-cored cut wire for groove filling, characterized in that the flux contains one or more strong deoxidizing elements selected from the group consisting of Ca, Mg, Ti, Zr, and REM as an oxide and / or alloy. (6) The total content of the oxide and / or alloy of the strong deoxidizing element is expressed as a mass ratio to the total mass of the flux-cored cut wire, The total content of the strong deoxidizing elements is 0.1% or more and 98.0% or less, and the contents of the chemical components consisting of C, Si, Mn, Cu, Ni, Cr, Mo, Nb, V, Al, B, and Bi are C: 0.120% or less, Si: 2.00% or less, Mn: 3.50% or less, Cu: 5.00% or less, Ni: 5.00% or less, Cr: 5.00% or less, Mo: 5.00% or less, Nb: 0.50% or less, V: 0.500% or less, Al: 1.70% or less, B: 0.020% or less, and Bi: 0.030% or less, The flux-cored cut wire for groove filling according to (5) above, characterized in that the contents of impurity elements consisting of P and S are P: 0.030% or less and S: 0.020% or less. (7) A flux-cored cut wire for groove filling according to (5) or (6) above, which is used by filling an initial layer in a groove provided between base materials. Effect of the Invention

[0013] According to the present invention, even when welding extremely thick high-strength steel plates, for example, it is possible to prevent hot cracking while reducing the burden of preheating, and further to manufacture a welded joint with advantageous welding efficiency. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is an explanatory diagram showing an example of a flux-cored cut wire welding process according to the present invention. [Diagram 2] FIG. 2 is an explanatory diagram showing another example of the flux-cored cut wire welding process according to the present invention. [Diagram 3] FIG. 3 is an explanatory diagram showing the groove shape used in the evaluation of hot cracking resistance in the examples and the state in which the flux-cored cut wire is filled into the groove. [Figure 4] FIG. 4 is an explanatory perspective view showing an observation piece for evaluation cut out from a test specimen prepared in the examples for the purpose of evaluating hot cracking resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention uses a flux-cored cut wire having a steel outer skin and flux filled inside the steel outer skin, and includes a flux-cored cut wire welding process in which the flux-cored cut wire is filled and welded into at least the first layer in a groove provided between base materials, thereby manufacturing a welded joint. Hereinafter, the flux-cored cut wire according to the present invention will be described, along with a method for manufacturing a welded joint using the same.

[0016] [Flux-cored cut wire] First, for the flux-cored cut wire, the flux used contains one or more strong deoxidizing elements selected from the group consisting of Ca, Mg, Ti, Zr, and REM (rare earth metals). These strong deoxidizing elements have the effect of significantly improving the hot cracking resistance of the weld metal. This is presumably because these strong deoxidizing elements form sulfides and remain in the weld metal. Since such strong deoxidizing elements (hereinafter sometimes referred to as "sulfide-forming elements") have a strong deoxidizing effect, even if they are added to ordinary welding wire or SAW flux, they become oxides in the deoxidizing reaction and are easily consumed, making it difficult to retain them in the weld metal with a good yield. However, it has been unexpectedly discovered that by using the flux-cored cut wire, they can be retained in the weld metal as sulfides with a good yield.

[0017] It is preferable to add one or more of these strong deoxidizing elements (Ca, Mg, Ti, Zr, and REM) to the flux-cored cut wire as oxides and / or alloys, and preferably as ferroalloys or oxides. By using them as oxides and / or alloys, the oxides are spherical and the alloys are easily deformed, so that the flux-cored cut wire is less likely to break during production, particularly when the wire is drawn. On the other hand, compounds other than oxides are often non-spherical, which increases the possibility of wire breakage. Incidentally, if nitrogen is contained as a compound, it may cause welding defects.

[0018] Here, in the flux-cored cut wire of the present invention, since the flux is filled inside (inside) of the steel sheath, strong deoxidizing elements (Ca, Mg, Ti, Zr, and REM) may be contained in large amounts. Therefore, the upper limit of the strong deoxidizing elements is not particularly limited. However, since the flux-cored cut wire is composed of the steel sheath and the flux filled inside (inside) of the steel sheath, the total content of the strong deoxidizing elements contained as oxides and / or alloys is preferably 0.1% or more and 98.0% or less in mass ratio to the total mass of the flux-cored cut wire. In addition, this upper limit may be 97.0%, 95.0%, or even 90.0%. Here, REM refers to a total of 17 elements, including 15 elements with atomic numbers 57 to 71 and two elements, Sc and Y, and any one of them or a mixture of two or more of them can be used. The content of REM is the total content of the 17 elements.

[0019] In addition, the flux-cored cut wire of the present invention may contain, in addition to the strong deoxidizing elements (Ca, Mg, Ti, Zr, and REM), alloy components (hereinafter, these chemical components and alloy components are simply referred to as "chemical components") for controlling the chemical components and carbon equivalent (Ceq) of the weld metal. In this case, these chemical components melt in the same manner as the steel sheath during welding. Therefore, the chemical components other than the strong deoxidizing elements may be contained in the flux in the form of metal powder or alloy powder, in the form of the steel sheath, or as plating on the outer surface of the steel sheath, and the same effect can be obtained regardless of the mode of addition. Note that the chemical components other than the strong deoxidizing elements do not need to be in the form of oxides or carbonates because arc stability and all-position weldability are not required as in the case of ordinary flux-cored wires that are not cut wires, and can be contained in the form of metal powder or alloy powder as described above.

[0020] Specifically, the flux-cored cut wire of the present invention has a total content of strong deoxidizing elements (Ca, Mg, Ti, Zr, and REM) of 0.1% or more and 98.0% or less in terms of mass ratio to the total mass of the flux-cored cut wire, and contains one or more chemical components selected from the group consisting of C, Si, Mn, Cu, Ni, Cr, Mo, Nb, V, Al, B, and Bi as optional components, and the content of each chemical component is C:0. 0.120% or less, Si: 2.00% or less, Mn: 3.50% or less, Cu: 5.00% or less, Ni: 5.00% or less, Cr: 5.00% or less, Mo: 5.00% or less, Nb: 0.50% or less, V: 0.500% or less, Al: 1.70% or less, B: 0.020% or less, and Bi: 0.030% or less, and the contents of the impurity elements P and S are preferably P: 0.030% or less and S: 0.020% or less, respectively. In the present invention, by containing the above-mentioned strong deoxidizing elements, hot cracking can be suppressed without containing any of the above-mentioned chemical components, so the lower limit of the content of each of these chemical components is 0%.

[0021] Among these, in the optional chemical components, C in "C: 0.120% or less" is an important element for ensuring the yield strength and tensile strength of the weld metal by solid solution strengthening. However, if the C content in the flux-cored cut wire exceeds 0.120%, the C content in the weld metal becomes excessive, and the yield strength and tensile strength of the weld metal increase excessively, resulting in a decrease in the toughness of the weld metal. In order to stably ensure all of the toughness, yield strength, and tensile strength of the weld metal, it is preferable to set the upper limit of this C content to 0.10%. On the other hand, the lower limit of the C content is 0%, but if necessary, the lower limit of the C content may be 0.010%, 0.020%, 0.030%, 0.040%, or 0.050%. Similarly, the upper limit of the C content may be 0.100%, 0.090%, 0.080%, or 0.070%.

[0022] The Si in "Si: 2.00% or less" is a deoxidizing element and has the function of reducing the amount of oxygen in the weld metal and increasing the cleanliness of the weld metal. If the Si content in the flux-cored cut wire exceeds 2.00%, Si deteriorates the toughness of the weld metal. In order to stably ensure the toughness of the weld metal, the upper limit of the Si content may be 1.90%, 1.80%, 1.70%, or 1.50%. On the other hand, the lower limit of the Si content is 0%, but if necessary, the lower limit of the Si content may be 0.01%, 0.02%, 0.03%, or 0.04%.

[0023] The Mn in "Mn: 3.50% or less" is an element necessary for ensuring the hardenability of the weld metal and increasing the strength of the weld metal, but it may be 0%. In order to increase the strength of the weld metal, the lower limit of the Mn content in the flux-cored cut wire may be set to 0.50%, 0.75%, or 1.0%. On the other hand, if the Mn content exceeds 3.50%, the susceptibility of the weld metal to grain boundary embrittlement increases and the toughness of the weld metal deteriorates. Therefore, although the upper limit of the Mn content is 3.50%, the upper limit of the Mn content may be set to 3.00%, 2.50%, or 2.00%.

[0024] The Cu in "Cu: 5.00% or less" has the effect of improving the strength and toughness of the weld metal, but may be 0%. Cu may be contained in the plating on the surface of the steel sheath of the flux-cored cut wire, or may be contained in the flux as a single element or as an alloy. This Cu content is the total amount of Cu contained in the steel sheath or flux and Cu contained in the plating on the surface. If this Cu content exceeds 5.00%, the toughness of the weld metal decreases. The upper limit of the Cu content is preferably 4.00%, 3.00%, or 2.00%. The lower limit of the Cu content is preferably 0.05%, 0.1%, or 0.15%.

[0025] In "Ni: 5.00% or less", Ni is not an essential component, so the lower limit of the Ni content in the flux-cored cut wire is 0%. If the Ni content is too high, solidification cracking is likely to occur. Therefore, the upper limit of the Ni content is preferably 4.00%, 3.00%, or 2.00%. The lower limit of the Ni content is preferably 0.05%, 0.1%, or 0.15%.

[0026] In "Cr: 5.00% or less", Cr is not an essential component, so the lower limit of the Cr content in the flux-cored cut wire is 0%. On the other hand, Cr increases the hardenability of the weld metal, so it is an effective element for improving the strength of the weld metal. In order to fully obtain this effect, it is preferable that the Cr content be 0.10% or more. Furthermore, if the Cr content exceeds 5.00%, the weld metal becomes excessively hard, deteriorating the toughness of the weld metal. The upper limit of the Cr content is preferably 4.00%, 3.00%, 2.00%, or 1.00%.

[0027] In "Mo: 5.00% or less", Mo is not an essential component, so the lower limit of the Mo content in the flux-cored cut wire is 0%. On the other hand, Mo has the effect of improving the hardenability of the weld metal, so it is an effective element for increasing the strength of the weld metal. In order to obtain this effect, the Mo content is preferably 0.01% or more. However, if the Mo content exceeds 5.00%, the toughness of the weld metal may deteriorate, so the Mo content is set to 5.00% or less. The upper limit of the Mo content is preferably 4.00%, 3.00%, 2.00%, 1.00%, or 0.60%.

[0028] In "Nb: 0.50% or less", Nb is not an essential component, so the lower limit of the Nb content in the flux-cored cut wire is 0%. On the other hand, Nb forms fine carbides in the weld metal, and these fine carbides cause precipitation strengthening in the weld metal, so Nb improves the tensile strength of the weld metal. In order to fully obtain this effect, it is preferable that the Nb content is 0.005% or more. However, it is not preferable for the Nb content to exceed 0.50%, because Nb forms coarse precipitates in the weld metal and deteriorates the toughness of the weld metal. The upper limit of the Nb content is preferably 0.40%, 0.30%, 0.20%, or 0.10%.

[0029] In "V: 0.500% or less", V is not an essential component, so the lower limit of the V content in the flux-cored cut wire is 0%. On the other hand, V improves the hardenability of the weld metal, so it is an effective element for increasing the strength of the weld metal. In order to fully obtain this effect, it is preferable that the V content is 0.010% or more. If the V content exceeds 0.500%, the amount of precipitation of V carbide in the weld metal becomes excessive, which causes the weld metal to become excessively hard, thereby deteriorating the toughness of the weld metal. The upper limit of the V content is preferably 0.400%, 0.300%, 0.200%, or 0.100%.

[0030] The Al in "Al: 1.70% or less" is a deoxidizing element, and like Si, it reduces the amount of oxygen in the weld metal and has the effect of improving the cleanliness of the weld metal. If the Al content in the flux-cored cut wire exceeds 1.70%, Al forms nitrides and oxides, etc., and reduces the toughness of the weld metal. Therefore, the upper limit of the Al content in the flux-cored cut wire is set to 1.70%. This upper limit is preferably 1.60%, 1.50%, 1.40%, or 1.30%. The lower limit of the Al content is preferably 0.005%, 0.010%, 0.050%, 0.100%, 0.150%, or 0.200%.

[0031] In "B: 0.020% or less", B is not an essential component, so the lower limit of the B content in the flux-cored cut wire is 0%. On the other hand, B combines with solute N in the weld metal to form BN, and therefore has the effect of reducing the adverse effect of solute N on the toughness of the weld metal. In addition, B increases the hardenability of the weld metal, and therefore has the effect of improving the strength of the weld metal. For this reason, the flux-cored cut wire may contain 0.0005% or more of B. However, if the B content exceeds 0.020%, the B in the weld metal becomes excessive, and coarse BN and Fe are generated. 23 This is undesirable because it forms B compounds such as (C, B)6 and deteriorates the toughness of the weld metal. The upper limit of the B content is preferably 0.015%, 0.010%, 0.005%, 0.003%, or 0.001%.

[0032] In "Bi: 0.020% or less", Bi is not an essential component, so the lower limit of the Bi content in the flux-cored cut wire is 0%. Meanwhile, Bi is an element that improves slag removability. To fully obtain this effect, the Bi content is preferably 0.005% or more, 0.010% or more, or 0.012% or more. Meanwhile, if the Bi content exceeds 0.020%, solidification cracking is likely to occur in the weld metal, so the upper limit of the Bi content is 0.020%. This upper limit of the Bi content is preferably 0.015%, 0.010%, or 0.005%.

[0033] Furthermore, since P, present as an impurity element in "P: 0.030% or less", reduces the toughness of the weld metal, it is necessary to reduce the P content in the flux-cored cut wire as much as possible. Therefore, the lower limit of the P content is 0%. Furthermore, if the P content is 0.030% or less, the adverse effect of P on the toughness falls within an allowable range. In order to prevent solidification cracking of the weld metal, the P content is more preferably 0.020% or less, 0.015% or less, or 0.010% or less.

[0034] In the "S: 0.020% or less" content of S present as an impurity element, if excessively present in the weld metal, it deteriorates both the toughness and ductility of the weld metal, so it is desirable to reduce the S content in the flux-cored cut wire as much as possible. Therefore, the lower limit of the S content is 0%. Furthermore, if the S content is 0.020% or less, the adverse effects of S on the toughness and ductility of the weld metal are within an acceptable range. More preferably, it is 0.010% or less, 0.008% or less, 0.006% or less, or 0.005% or less.

[0035] The flux-cored cut wire of the present invention may or may not contain the chemical components described above. In addition to these chemical components, the strong deoxidizing elements (Ca, Mg, Ti, Zr, and REM), and impurity elements, the flux cored cut wire contains Fe and impurities. Among these, Fe may be contained in iron powder in addition to the steel sheath. That is, in order to adjust the flux filling rate in the flux cored cut wire or to improve the welding efficiency, the flux may contain iron powder as necessary. The content of this iron powder is not particularly limited, but since oxygen attached to the surface layer of the iron powder may increase the oxygen content of the weld metal and reduce the toughness, it is preferable that the mass ratio of the flux cored cut wire to the total mass is less than 90.0%, preferably less than 80.0%. The upper limit of the content of iron powder may be limited to 8.0%, 6.0%, 4.0%, 2.0%, or 1.0%. Of course, since iron powder is not essential in the flux-cored cut wire according to the present invention, the lower limit of the iron powder content is 0%.

[0036] The impurities are components that are introduced into the flux-cored cut wire during industrial production due to the raw materials or various factors in the production process, and are allowed to exist within a range that does not adversely affect the flux-cored cut wire according to the present invention.

[0037] The flux-cored cut wire of the present invention may contain fluorides, oxides, carbonates, etc. of other metal elements other than the strong deoxidizing elements, chemical components, and impurity elements described above, to the extent that the characteristics are not impaired. In this case, the fluorides, oxides, and carbonates of the other metal elements are not included in the contents of the strong deoxidizing elements, chemical components, impurity elements, and Fe and impurities. However, this does not mean that the fluorides, oxides, and carbonates of these other metal elements are contained. That is, the flux-cored cut wire of the present invention has a chemical composition that contains the strong deoxidizing elements described above at a predetermined ratio, the contents of the chemical components and impurity elements described above are each within a predetermined range, and the balance is Fe and impurities, or Fe, impurities, and fluorides, oxides, and carbonates of these other metal elements. Preferably, the flux-cored cut wire has a chemical composition that contains the strong deoxidizing elements described above at a predetermined ratio, the contents of the chemical components and impurity elements described above are each within a predetermined range, and the balance is Fe and impurities.

[0038] Furthermore, as long as the above-mentioned conditions are satisfied, the steel sheath of the flux-cored cut wire according to the present invention is not particularly limited. For example, when the steel sheath is made of a mild steel sheath, the chemical composition of the sheath can be, by mass percentage, C: 0.1% or less, Si: 0.10% or less, Mn: 3.00% or less, P: 0.030% or less, S: 0.020% or less, Al: 0.1% or less, and N: 0.030% or less, with the remainder being iron and impurities.

[0039] The flux-cored cut wire of the present invention can be obtained by forming a wire shape in a state where a steel sheath is filled with flux, and then cutting it into pieces to a predetermined length. There is no particular restriction on the shape of the cut flux-cored cut wire, and a thin-diameter steel wire can be cut into pieces to a predetermined length to make it approximately the same as a general cut wire with a circular cross section, but considering that the flux is filled, the diameter is preferably φ1.0 to φ3.0 mm. Incidentally, the diameter of a conventional cut wire is about φ1.0 to φ2.0 mm. On the other hand, the length of the flux-cored cut wire is preferably 0.5 to 3.5 mm. In the case of a general cut wire, the length is equivalent to 0.5 to 2.0 times the wire diameter.

[0040] The flux filling rate is not particularly limited as long as the above-mentioned conditions are satisfied. For example, the lower limit of the flux filling rate, expressed as a mass ratio to the total mass of the flux-cored cut wire, may be 10% or 12%. The upper limit of the flux filling rate may be 80% or 90%.

[0041] Here, in order to reduce the amount of diffusible hydrogen in the weld metal, it is preferable that the amount of hydrogen contained in the flux-cored cut wire is 12 ppm or less relative to the total mass of the flux-cored cut wire. This amount of hydrogen intrudes during the manufacture of the flux-cored cut wire, and may also increase due to moisture intrusion during storage of the flux-cored cut wire. Therefore, if the period between the manufacture of the cut wire and its use is long, it is desirable to store the wire while preventing moisture intrusion.

[0042] The procedure for producing the flux-cored cut wire of the present invention is not particularly limited, but the following example can be given as a method for producing flux-filled wire before cutting. First, a method for producing a seamless flux-cored cut wire in which the seam of the steel sheath is welded to have no slit-like gaps includes the steps of preparing the flux so that the strong deoxidizing elements and chemical components are within a predetermined range, forming the steel strip using a forming roll while feeding the steel strip in the longitudinal direction to obtain a U-shaped open tube, supplying the flux into the open tube through the opening of the open tube, butt-welding the opposing edges of the opening of the open tube to obtain a seamless tube, drawing the seamless tube to obtain a flux-cored wire with a predetermined wire diameter, and annealing the flux-cored wire during or after the drawing step. The wire is then cut to a predetermined length to obtain the flux-cored cut wire.

[0043] Here, the butt welding is performed by electric resistance welding, laser welding, TIG welding, or the like. In addition, annealing is performed during the wire drawing process or after the wire drawing process is completed to remove moisture in the wire. Preferably, the annealing temperature is 650°C or higher and the annealing time is 4 hours or longer to make the H content in the wire 12 ppm or less. However, in order to prevent deterioration of the flux, the annealing temperature is 900°C or lower. Note that, instead of butt welding, a wire without slit-shaped gaps can be obtained by brazing the gaps in the steel sheath.

[0044] Also, the seam of the steel sheath may not be welded to obtain a flux-cored cut wire with a slit-shaped gap. In that case, the method is the same as the method for manufacturing a wire having a seamless shape, except that instead of the step of butt-welding the ends of an open pipe to obtain a seamless pipe, a step of forming an open pipe and butting the ends of the open pipe to obtain a pipe with a slit-shaped gap is included. The method for manufacturing a wire having a slit-shaped gap may further include a step of crimping the butted ends of the open pipe. In the method for manufacturing a wire having a slit-shaped gap, a pipe is drawn in a state in which a slit-shaped gap is present.

[0045] As described above, the flux-cored cut wire according to the present invention may be a wire cut from a seamless shape in which the seam of the steel sheath is welded and there is no slit-shaped gap, or a wire cut from a wire in which the seam of the steel sheath is not welded and there is a slit-shaped gap. However, it is preferable that the flux-cored cut wire is a wire cut from a steel sheath having no slit-shaped gap. H (hydrogen) that penetrates the welded part during welding diffuses into the weld metal and the welded material, accumulates in the stress concentration part, and causes cold cracking. There are various sources of H, but if the cleanliness of the welded part and the welding conditions are strictly controlled, the moisture (H2O) contained in the flux-cored cut wire can be a source of H, and the amount of this moisture may affect the amount of diffusible hydrogen in the welded joint. Therefore, a wire cut from a seamless shape in which there is no slit-shaped gap is preferable, but if the wire cut from a wire having a slit-shaped gap is cut, the flux-cored cut wire may be stored, for example, in a vacuum package or in a container that can maintain a dry state.

[0046] The flux-cored cut wire of the present invention may have an oil (lubricant) applied to its surface. The lubricant applied to the filler surface has the effect of suppressing rust generation during storage. Various types of lubricants (e.g., vegetable oils such as palm oil) can be used as such lubricants, but in order to suppress low-temperature cracking of the weld metal, it is preferable to use perfluoropolyether oil (PFPE oil) that does not contain H (hydrogen). When the flux-cored cut wire has a plating on its surface, the lubricant is applied to the plating surface.

[0047] [Method of manufacturing welded joints] Next, in manufacturing a welded joint using the above-mentioned flux-cored cut wire, the present invention includes a flux-cored cut wire welding process in which at least the first layer in a groove provided between base materials is filled with flux-cored cut wire and welded. That is, in manufacturing a welded joint, in the case where welding is performed using a plurality of passes, the flux-cored cut wire according to the present invention is filled in the groove of the base materials and welded at least in the first pass, and the flux-cored cut wire according to the present invention is used up to the middle of the groove as necessary in the second pass and thereafter. In addition, in the case where welding is performed using only one pass, the flux-cored cut wire according to the present invention is used in that one pass.

[0048] In particular, in the flux-cored cut wire welding process, it is preferable to fill at least the first layer in the groove with the flux-cored cut wire according to the present invention and perform welding. That is, by filling the first layer in the groove, where the probability of hot cracking is high, with the flux-cored cut wire, hot cracking can be prevented.

[0049] An example of a flux-cored cut wire welding process according to the present invention is shown in Figures 1 and 2. Of these, Figure 1 shows an example in which a flux-cored cut wire 4 is filled into an initial layer in a groove 3 provided between base materials 1 and 2, and welding is performed.

[0050] First, as shown in Fig. 1(a), a backing material 5 is attached to the back surface of base materials 1 and 2, and then a flux-cored cut wire 4 according to the present invention is filled into the first layer in a groove 3. Then, as shown in Fig. 1(b), a welding wire is placed on top of the filled flux-cored cut wire 4 and welding is performed. When hot cracking resistance is required only in the first layer, as shown in Fig. 1(c), welding is performed on top of the weld metal 7 obtained including the flux-cored cut wire 4 filled into the first layer without using the flux-cored cut wire of the present invention.

[0051] Furthermore, when hot cracking resistance is required not only for the initial layer but also for intermediate layers, as shown in Figs. 1(d) to 1(f), welding is performed up to the required intermediate layer on top of the initial layer weld metal 7 obtained including the flux-cored cut wire 4 using a further flux-cored cut wire 4, and then welding is performed without using the flux-cored cut wire of the present invention.

[0052] As shown in FIG. 2, the flux-cored cut wire welding process according to the present invention may be performed by flux-cored cut wire filling one-pass welding in which a flux-cored cut wire is filled in the groove and welding is performed in one pass. That is, as shown in Fig. 2(a), a backing material 5 is attached to the back surface of the base materials 1 and 2, and then the flux-cored cut wire 4 according to the present invention is dispersed so as to fill almost the entire inside of the groove 3, for example, about 70% of the height inside the groove, in the example of Fig. 2. Next, as shown in Fig. 2(b), a welding wire 6 is placed approximately on the center of the filled flux-cored cut wire 4, and an arc is generated to perform welding, thereby producing a welded joint by a weld metal 7 containing the flux-cored cut wire 4, as shown in Fig. 2(c). In the example of the flux-cored cut wire welding process shown in FIG. 2, the flux-cored cut wire according to the present invention is used in almost the entire groove.

[0053] 1 and 2 show an example in which the groove between the base materials is a so-called V-shaped groove, but the groove shape is not limited to this in the present invention, and other groove shapes such as I-shaped, L-shaped, K-shaped, J-shaped, X-shaped, U-shaped, H-shaped, and other groove shapes may be used. In addition, the present invention may be applicable to both single-sided welding and double-sided welding. Furthermore, in the case of multi-layer welding as in the example of FIG. 1, each layer may be welded in two or more passes.

[0054] The welding method (welding means) used in the present invention is not particularly limited, but in order to reliably melt the flux-cored cut wire filled in the groove, it is preferable to use submerged arc welding or gas-shielded arc welding. However, since it may be difficult to fill the groove with the flux-cored cut wire in vertical welding or overhead welding, the welding position is preferably downward or sideways.

[0055] In addition, the method for manufacturing a welded joint according to the present invention is not particularly limited in terms of the type or shape of the base material, but is most effective when applied in situations where hot cracking is a problem. That is, a representative example is welding of a base material made of high-strength steel with a tensile strength of 780 MPa or more. In particular, it can be said that the application of the present invention is extremely effective in cases where narrow grooves are to be welded in one pass. The combination of base materials forming the groove is arbitrary, and may be the same type of base material or different base materials.

[0056] In addition, while a typical method for manufacturing a welded joint produces a welded joint having a base steel plate (base material) and a welded joint consisting of a weld metal and a weld heat-affected zone, the present invention uses a flux-cored cut wire that further contains specified chemical components, thereby making it possible to produce a welded joint with high strength and toughness.

[0057] (Example) Next, the present invention will be described in more detail with reference to examples. However, the following examples are not intended to limit the present invention, and any design modifications made within the spirit of the invention are within the technical scope of the present invention.

[0058] The flux-cored cut wires of the present invention and comparative examples (samples with wire numbers 1 to 42) were produced by the following method. First, a steel strip was fed in the longitudinal direction and formed using a forming roll to obtain a U-shaped open tube. Flux was supplied into the open tube through the opening, and the opposing edges of the opening of the open tube were butt-welded to obtain a seamless tube. This seamless tube was drawn to obtain a flux-cored wire without slit-shaped gaps. However, at this time, some samples were made into tubes with slit-shaped gaps without seam welding, and these were drawn to obtain wire. In this way, a flux-cored wire with a final filler diameter of φ2.0 mm was produced. During the wire drawing process, the flux-cored wires were annealed for 4 hours or more at a temperature range of 650 to 950°C. After the prototypes were made, a lubricant was applied to the surface of some of the wires. The manufactured flux-cored wires were then cut to a length of 2.0 mm to prepare samples of flux-cored cut wires. In preparing the flux, with regard to the sulfide-forming elements (strong deoxidizing elements) shown in Table 1, Ca, Mg, and Ti were used as metal (alloy) powder, and the REM elements Ce and La were used as their oxides, and the amounts are shown in Tables 1 and 2 in terms of the mass proportions of each element. The compositions of these flux-cored cut wires are shown in Tables 1 and 2. (Of these, wire numbers 8 to 12 and 32 correspond to reference examples.) .

[0059] [Table 1]

[0060] [Table 2]

[0061] The units of the contents of the strong deoxidizing elements (sulfide-forming elements), optional chemical components, iron powder (Fe powder), and each element contained as an impurity element listed in Tables 1 and 2 are the mass percentage (mass%) relative to the total mass of the flux-cored cut wire.

[0062] The balance in the chemical composition of the flux-cored cut wires (i.e., components other than the elements disclosed in Tables 1 and 2) is iron (including intentionally added Fe powder) and impurities. The wire structure of each flux-cored cut wire is as shown in Table 1, and unless otherwise specified in the remarks column, no oil is applied. Meanwhile, each element contained as a chemical component in the flux-cored cut wires disclosed in Table 2 is contained in the steel sheath or flux in the form of metal powder and / or oxide powder. In Tables 1 and 2, the blanks in the tables for the contents of strong deoxidizing elements, chemical components, and Fe powder mean that the strong deoxidizing elements, chemical components, and Fe powder are not intentionally added. However, strong deoxidizing elements and chemical components may be unavoidably mixed in.

[0063] Welded joints were produced using the flux-cored cut wires of the invention and comparative examples by the methods described below, and were evaluated by the methods described below. A welded joint test specimen was produced by performing SAW welding in one pass under the welding conditions in Table 3 on a steel sheet having a plate thickness of 20 mm and a tensile strength of 490 MPa. The groove shape was a V-shape as shown in Fig. 3, and the thickness of the flux-cored cut wire 4 spread in the groove 3 was 16 mm. Furthermore, NF-100 manufactured by Nippon Steel & Sumitomo Metal Welding Co., Ltd. was used as the welding flux, and Y-DS (wire diameter φ4.8 mm) manufactured by Nippon Steel & Sumitomo Metal Welding Co., Ltd. was used as the welding wire. The welding wire was set perpendicular to the steel sheet.

[0064] [Table 3]

[0065] [Evaluation of hot cracking resistance] For the evaluation of hot cracking resistance, as shown in Figure 4, the prepared test specimen was cut at five locations every 50 mm within a range of 300 mm in length excluding the start and end parts of the weld bead, to prepare five evaluation specimens 8 in which the cross section of the weld metal 7 portion (weld metal cross section) had the same V-shaped cross section as the groove shape, and the macrostructure of the weld metal cross section of each evaluation specimen 8 was observed. Those in which no cracks occurred in any of the weld metal cross sections of these five evaluation specimens 8 were rated as "passed," and those in which cracks occurred in one or more cross sections were rated as "failed." The test results evaluated by the above-mentioned methods are shown in Table 4.

[0066] [Evaluation of the yield of strong deoxidizing elements (sulfide-forming elements)] First, a test piece measuring 10 mm x 10 mm x 5 mm was taken from near the center of the weld metal, and the surface of a 10 mm x 10 mm area, which is a cross section perpendicular to the welding direction, was mirror-polished and observed. The surface of the test piece was observed by SEM / EDX (scanning electron microscope / energy dispersive X-ray spectroscopy) analysis using a JEOL "JXA-8530F". The observation conditions were an acceleration voltage of 15 kV, a current of 89 to 91 μA, and an observation field area of ​​25 mm. 2 , and the number of analyses was 100 or more.

[0067] The analyzed elements were O, S, Ca, Mg, Ti, Zr, and REM, and the mass ratio (mass%) of each analyzed element to the total mass of these analyzed elements was calculated. Here, inclusions in which the mass% of S was 1.0 mass% or more and at least one of the strong deoxidizing elements Ca, Mg, Ti, Zr, and REM was 1.0 mass% or more were defined as "sulfide-containing inclusions." The density of the sulfide-containing inclusions is 10 / mm 2 The above cases were evaluated as those in which the strong deoxidizing elements remained in the weld metal as sulfides with good yield. Table 4 shows the results of the yield of strong deoxidizing elements evaluated by the above-mentioned method.

[0068] When welding was performed using the flux-cored cut wire of the present invention, the evaluation of hot cracking resistance was rated (passed) as no cracks were observed in any cross section (no cross-sectional cracks occurred). In other words, it was confirmed that the flux-cored cut wire of the present invention has extremely high hot cracking resistance. On the other hand, when the comparative flux-cored cut wire was used, the evaluation of hot cracking resistance showed that cracks were present (cross-sectional cracks occurred) in both cross sections (failure).

[0069] [Table 4]

[0070] As described above, according to the present invention, it is possible to prevent hot cracking even when welding high-strength steel plates, and it is possible to manufacture welded joints with high welding efficiency, which is advantageous in terms of the working environment and cost. [Explanation of symbols]

[0071] 1, 2...base material (steel), 3...groove, 4...flux-cored cut wire, 5...backing material, 6...welding wire, 7...weld metal, 8...observation piece for evaluation.

Claims

1. A method for manufacturing a welded joint in which a cut wire is filled into a groove provided between base materials and welded, A method for welding by filling a first layer in the groove with a flux-cored cut wire having a steel sheath and flux filled inside the steel sheath, The flux contains one or more strong deoxidizing elements selected from the group consisting of Ca, Mg, Ti, Zr, and REM as an oxide and / or an alloy, The flux-cored cut wire has a mass ratio relative to the total mass of the flux-cored cut wire of: The total content of the strong deoxidizing elements is 11.0% or more and 98.0% or less, and the contents of the chemical components consisting of C, Si, Mn, Cu, Ni, Cr, Mo, Nb, V, Al, B, and Bi are C: 0.120% or less, Si: 2.00% or less, Mn: 3.50% or less, Cu: 5.00% or less, Ni: 5.00% or less, Cr: 5.00% or less, Mo: 5.00% or less, Nb: 0.50% or less, V: 0.500% or less, Al: 1.70% or less, B: 0.020% or less, and Bi: 0.030% or less, A method for manufacturing a welded joint, characterized in that the contents of impurity elements consisting of P and S are P: 0.030% or less and S: 0.020% or less.

2. The method for manufacturing a welded joint according to claim 1, characterized in that the welding is submerged arc welding or gas shielded arc welding.

3. A cut wire for groove filling that fills a groove between base materials to manufacture a welded joint, A steel sheath and a flux filled inside the steel sheath, The flux contains one or more strong deoxidizing elements selected from the group consisting of Ca, Mg, Ti, Zr, and REM as an oxide and / or an alloy, The total content of the oxide and / or alloy of the strong deoxidizing element is expressed as a mass ratio to the total mass of the flux-cored cut wire, The total content of the strong deoxidizing elements is 11.0% or more and 98.0% or less, and the contents of the chemical components consisting of C, Si, Mn, Cu, Ni, Cr, Mo, Nb, V, Al, B, and Bi are C: 0.120% or less, Si: 2.00% or less, Mn: 3.50% or less, Cu: 5.00% or less, Ni: 5.00% or less, Cr: 5.00% or less, Mo: 5.00% or less, Nb: 0.50% or less, V: 0.500% or less, Al: 1.70% or less, B: 0.020% or less, and Bi: 0.030% or less, A flux-cored cut wire for groove filling, characterized in that the contents of impurity elements P and S are P: 0.030% or less and S: 0.020% or less.

4. The flux-cored cut wire for groove filling according to claim 3, which is used by filling an initial layer in a groove provided between base materials.

Citation Information

Patent Citations

  • JP1974016023A

  • Starting method for electroslag welding

    JP1986216881A

  • Game machine

    JP2008000264A

  • Sealed container and conveyance system

    JP2016000022A